1999
DOI: 10.1038/10165
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between β2-syntrophin and a family of microtubule-associated serine/threonine kinases

Abstract: A screen for proteins that interact with beta 2-syntrophin led to the isolation of MAST205 (microtubule-associated serine/threonine kinase-205 kD) and a newly identified homologue, SAST (syntrophin-associated serine/threonine kinase). Binding studies showed that beta 2-syntrophin and MAST205/SAST associated via a PDZ-PDZ domain interaction. MAST205 colocalized with beta 2-syntrophin and utrophin at neuromuscular junctions. SAST colocalized with syntrophin in cerebral vasculature, spermatic acrosomes and neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
109
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(111 citation statements)
references
References 46 publications
(46 reference statements)
2
109
0
Order By: Relevance
“…In addition, recent studies (1)(2)(3)(4)(5)(6)(7) have shown that the dystrophin complex is critical for the localization of a variety of signaling molecules to the skeletal muscle sarcolemma. Thus, the dystrophin complex functions as both a structural link to the extracellular matrix and as a scaffold that concentrates and stabilizes functionally inter-related signaling proteins at the muscle cell membrane.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies (1)(2)(3)(4)(5)(6)(7) have shown that the dystrophin complex is critical for the localization of a variety of signaling molecules to the skeletal muscle sarcolemma. Thus, the dystrophin complex functions as both a structural link to the extracellular matrix and as a scaffold that concentrates and stabilizes functionally inter-related signaling proteins at the muscle cell membrane.…”
mentioning
confidence: 99%
“…Of these, the syntrophins are the best characterized and are involved in signaling by recruiting neuronal nitric-oxide synthase (1,24), ion channels (6), and kinases (3,5) to the dystrophin complex. Whether syncoilin, desmuslin, or dysbindin contributes to the signaling function of dystrobrevin and the dystrophin complex remains to be seen.…”
mentioning
confidence: 99%
“…At neuromuscular synapses MAST205 interacts with ␤-2 syntrophin (1,2). In addition to a well conserved protein kinase C/A kinase domain, MAST205 has a PDZ domain, a protein-protein recognition module (3).…”
mentioning
confidence: 99%
“…Dystrophin/utrophin bind other intracellular members of the DGC: dystrobrevin (which in turn binds neuronal nitric oxide synthase / nNOS, dysbindin , syncoilin and DAMAGE (Albrecht and Froehner, 2004a)), and syntrophin (binds Calmodulin, Na + channels (Gee et al, 1998b), the potassium channel Kir4.1 (Connors et al, 2004a), Grb2, ErbB4, MAST/SAST (Yano et al, 2003;Lumeng et al, 1999b) and might also be responsible for the correct localisation of aquaporin-4 (Neely et al, 2001)). Localisation: Dystrobrevin has been found to be expressed in the developing and adult brain (Lien et al, 2004;Enigk and Maimone, 1999) and retina (Blank et al, 2002).…”
Section: Utrophinmentioning
confidence: 99%